Carrying, keeping and use of masculine preservative among young people in Fortaleza - a descriptive study - Ana Luiza Santos de Carvalho; Saiwori de Jesus da Silva Bezerra; Nilza Maria de Abreu Leitão; Mirella Teixeira Joca; Ana Karina Bezerra Pinheiro (Universidade Federal Fluminense, Escola de Enfermagem Aurora de Afonso Costa, 2007)
It was aimed to verify carrying, keeping and frequency of use of the masculine preservative among young night club goers in the city of Fortaleza, Ceará. Research traverse of the exploratory-descriptive type of quantitative approach. Population constituted by 211 young night club goers older than 18 years. The data were stored and codified in SPSS. It was observed 124 (58,8%) reported always to use preservatives. Of those who referred to use it not frequently, the main reason for not accepting it was the use of the hormonal contraceptive (43,2%). Of the interviewed people, 130 (61,6%) weren't carrying preservative and 81 (38,4%) were carrying. 40,7% kept it in the wallet. There was a relationship between the way the preservative was kept and the conditions of the package because those crumpled were all kept in the wallet. It was verified the importance of the discussion of this issue among young, a way of contributing for the reduction of infections, given that these present people risk behavior for DST/AIDS.